Barsine insolita, a new species from Indochina and India (Lepidoptera, Erebidae, Arctiinae) - Volynkin, Anton V.; Černý, Karel; Im, Kyung-Hoan; Bae, Yang-Seop; Bayarsaikhan, Ulziijargal (Zootaxa, 2019)
Barsine Walker, 1854 is one of the largest quadrifid Erebidae genera within subtribe Nudariina (Erebidae, Arctiinae, Lithosiini). It was established for its type species Barsine defecta Walker, 1854 (by subsequent designation, Kirby (1892)) from Nepal. The genus has in the past been treated as a synonym or subgenus of Miltochrista Hübner, [1819] (Hampson 1900; Strand 1917; Reich 1937; Daniel 1951; 1952; 1955; Inoue 1980; Holloway 1982; Fang 1991; 2000; Černý 1995). In 2001, J.D. Holloway revived Barsine as a distinct genus. The genus is widely distributed in eastern and southeastern Palaearctic and Oriental tropics and more than a hundred of valid species and subspecies were worked on by Fang (2000), Holloway (2001), Kaleka (2003), Černý & Pinratana (2009), Černý (1995, 2016), Bucsek (2012, 2014), Dubatolov et al. (2012), Dubatolov & Bucsek (2013), Wu et al. (2013), Kirti & Singh (2015, 2016), Volynkin & Černý (2016a, 2016b, 2016c, 2017a, 2017b, 2017c, 2017d, 2018a, 2018b; 2019), Bayarsaikhan et al. (2018), Joshi et al. (2018), Spitsyn et al. (2018), Volynkin (2018), Volynkin et al. (2018; 2019a; 2019b; 2019c) and Huang et al. (2018).